Captive breeding and release diminishes genetic diversity in Brown Teal Anas chlorotis, an endangered New Zealand duck - Bowker-Wright, Gemma; Bell, Ben D; Ritchie, Peter A; Williams, Murray (Wildfowl, 2012)
We examined levels of mitochondrial DNA (mtDNA) and DNA microsatellite genetic variation in Brown Teal (Anas chlorotis), mainland New Zealand’s rarest waterfowl. Samples were taken from the two remaining wild populations, a captive population, and four new populations established by released captive offspring. The larger wild population on Great Barrier Island (GBI) had two mtDNA haplotypes, one very rare, perhaps indicative of a historic bottleneck. The captive population was founded exclusively from GBI individuals; it and all new populations contained only the common GBI haplotype. In contrast, the smaller wild population at Mimiwhangata (MIW), Northland, contained 11 mtDNA haplotypes, including the common GBI haplotype which was probably introduced by captive-sourced releases 18–20 years ago. Microsatellite allelic richness was high in wild populations compared with captive and new populations. We suggest that genetic supplementation should be considered for the captive and new populations, and that the long-term goals of the Brown Teal recovery programme would benefit from assiduous and persistent genetic management and monitoring.